Music consumption among English speaking teenage girls in the city of Montreal - Giles, Jennifer (Université Carleton, 1987)
Music Consumption among English Speaking Teenage Girls in the City of Montreal

Theorizing music's affective power - Giles, Jennifer; Shepherd, John (Ethnomusicology in Canada, 1990)